Competitive Advantage in the World of Wine—An Analysis of Differentiation Strategies Developed by Sectoral Brands in the Global Market - Daniel Marian Micu; Georgiana Armenița Arghiroiu; Ștefan Micu; Silviu Beciu (Foods)
This study aims to analyze the differentiation strategies developed by sectoral brands in the global wine industry and how these strategies interrelate. A sectoral brand is defined as having a distinctive brand name accompanied by a visual identity, with or without a slogan. Through an analysis of thirty-three sectoral brands developed by wine-producing countries, seven clusters of differentiation strategies and three clusters of differentiation attributes were identified, using quantitative and qualitative methods. The findings highlight the alignment between the differentiation strategies employed by sectoral brands and the underlying theoretical concepts, as well as overlaps between differentiation strategies and specific attributes. The results identify unrevealed opportunities for wine-producing countries that have not yet developed sectoral brands. This study’s main contribution consists of the application of a cluster analysis approach, which enabled the identification and interpretation of relationships among sectoral wine brands based on their differentiation strategies. Accordingly, the research addresses a notable gap in the existing literature by providing an integrative perspective on how sectoral brands differentiate within the world wine market. The practical implications of this study include offering valuable guidance to countries currently lacking sectoral wine brands and presenting a structured framework to effectively leverage unique national attributes.